Teacher and learner preparedness to integrating ICTS in the teaching of FET-Phase geography during Covid-19 - Gubevu, B. (South African Journal of Higher Education, 2025)
This article examines teacher and learner preparedness in the integration of ICTs (information and communication technologies), in the teaching and learning of Geography in the Further Education and Training (FET) phase, in the South African context, during the Covid-19 pandemic. The article is underpinned by the Will Skill Tool Model of ICT integration, which proved to be a key tool in measuring readiness for ICT integration during the pandemic. The qualitative research approach was used to gain an in–depth understanding of learners’ and teachers’ views on whether they were ready to integrate ICTs in the teaching of FET–phase Geography during this period. Case study design was employed to determine the contexts of the participants’ perceptions. The researchers employed purposive sampling, interviews, and document reviews to collect data. The study results revealed the participants’ under–preparedness to implement ICTs and identified a lack of support from educational authorities in providing teachers with the necessary skills and infrastructure to level the playing field for integrating ICTs in Geography classrooms. To empower participants to participate in the global village, officials need to fact–track ICT–integration policy development, implementation, and monitoring, and to improve and provide adequate ICT infrastructure in schools, irrespective of their location.